Fundamentals of 2, 4 Dichlorophenoxyacetic Acid Removal from Aqueous Solutions. Issue 4 (2nd October 2018) - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.
Abstract : Herbicides are widely used in farmlands worldwide. However, after their application on farmlands, they accumulate in high amounts in continental and marine waters. Herbicides are endocrine disruptors, and are known to cause toxicity, carcinogenicity and mutagenicity. Besides, they also spoil the taste and odor of water bodies. To prevent these effects, it is necessary to perform an in-depth study on various herbicide removal methods. This review discusses the various methods of herbicide removal from aqueous body, using a commonly used herbicide (2, 4-dichlorophenoxyacetic acid) as a representative chemical. This paper includes a systematic tabulated review of all reported removal methods with important parameters and their mechanism. Adsorption, biological degradation, electrochemical treatment, Fenton degradation, oxidation, ozonation and photocatalytic degradation are investigated and compared for removal of 2, 4-D. The advantages and disadvantages and the factors influencing selection of the aforementioned processes are discussed.